PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MAHASISWA MEMILIH STMIK IBBI MEDAN - Adriasan Sudarso; Lili Suryaty (Politeknik Negeri Sriwijaya, 2014)
The purpose of these research is to test dan to prove the influence of marketing mix (product (study program), price (tuition fee), promotion, place, people, process, and service) toward students decision for choosing the School of Computers IBBI Medan. The type of these research is assosiative descriptive with clausal connected. Data were colleted based on proportionate stratified random sampling of 308 respondents from two study programs, namely S1 Information System (204 students) and S1 Informatica Tehnics (104). The research instruments used was a likert scale in which the validity and realibility were using the SPSS version 17. Result if these statistical analysis showed that the F calculated was orang bigger than F-Tabel which was 2.040, showing that the Product(study program), Price(tuition fee), promotion, place, process, and service had a significant influence on students decision for enrolling the School of Computers IBBI Medan. Based on these research we take a conclusion that was an Marketing Mix such as product, promotion, price, place, process, service that have a significant student decide to enroll at the school of Computers (STMIK) IBBI as a accepting place for their study.And people had not significant influence on students decision for enrolling the School of Computers IBBI Medan.